2015
DOI: 10.1088/0004-637x/814/1/76
|View full text |Cite
|
Sign up to set email alerts
|

SIMULATOR OF GALAXY MILLIMETER/SUBMILLIMETER EMISSION (SÍGAME): THE [C ii]–SFR RELATIONSHIP OF MASSIVEz= 2 MAIN SEQUENCE GALAXIES

Abstract: We present SÍGAME simulations of the C II [ ] 157.7 μm fine structure line emission from cosmological smoothed particle hydrodynamics simulations of seven main sequence galaxies at z=2. Using sub-grid physics prescriptions the gas in our simulations is modeled as a multi-phased interstellar medium comprised of molecular gas residing in giant molecular clouds, an atomic gas phase associated with photo-dissociation regions (PDRs) at the cloud surfaces, and a diffuse, ionized gas phase. Adopting logotropic cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 112 publications
(228 reference statements)
4
79
0
Order By: Relevance
“…The GMC sizes (R GMC ) are derived from a pressure-normalized mass-size relation (Olsen et al 2015), which results in cloud radii in the range 5.8 to 43.6 pc (Fig. 3).…”
Section: Cosmological Galaxy Formation Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GMC sizes (R GMC ) are derived from a pressure-normalized mass-size relation (Olsen et al 2015), which results in cloud radii in the range 5.8 to 43.6 pc (Fig. 3).…”
Section: Cosmological Galaxy Formation Simulationsmentioning
confidence: 99%
“…For the diffuse clouds we exclude turbulence by setting it to 0 km s −1 , after a test showed that setting the turbulence to 10 km s −1 only decreases the [C II] luminosities by on average 0.07 dex. For the GMCs we use the velocity dispersion obtainable from the cloud radius and pressure (see Olsen et al 2015).…”
Section: Gas Kinetic Temperaturementioning
confidence: 99%
“…In our work we did not take the contribution from ionised regions to the [CII] emission of galaxies into account. Olsen et al (2015b) applied a radiative transfer code to seven modeled main-sequence galaxies at z = 2. The authors compute the contribution to the total [CII] emission from PDRs, atomic, and ionised regions and found that the [CII] emission from ionised regions only accounts for a few percent of the total [CII] luminosity.…”
Section: [Cii] Emission From Ionised Regionsmentioning
confidence: 99%
“…From the theoretical side, the issue of non-detections has been studied, e.g., by Vallini et al (2015), Olsen et al (2015), and Narayanan & Krumholz (2016). Both Vallini et al (2015) and Olsen et al (2015) conclude that in high-z galaxies the [C II] emission arises predominately from photodissociation regions.…”
Section: Introductionmentioning
confidence: 99%